4+3n=n-7+n

Simple and best practice solution for 4+3n=n-7+n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+3n=n-7+n equation:


Simplifying
4 + 3n = n + -7 + n

Reorder the terms:
4 + 3n = -7 + n + n

Combine like terms: n + n = 2n
4 + 3n = -7 + 2n

Solving
4 + 3n = -7 + 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
4 + 3n + -2n = -7 + 2n + -2n

Combine like terms: 3n + -2n = 1n
4 + 1n = -7 + 2n + -2n

Combine like terms: 2n + -2n = 0
4 + 1n = -7 + 0
4 + 1n = -7

Add '-4' to each side of the equation.
4 + -4 + 1n = -7 + -4

Combine like terms: 4 + -4 = 0
0 + 1n = -7 + -4
1n = -7 + -4

Combine like terms: -7 + -4 = -11
1n = -11

Divide each side by '1'.
n = -11

Simplifying
n = -11

See similar equations:

| 3+5m=8m-105 | | 3x+5=3(2x+4)+3x | | -79+x+9x=41 | | .04x+.2(6-x)=.08(6) | | -3(4t-2)+5t=6t-8 | | D=5d-6 | | 1=.5x*3.61 | | 8+2(3x-2)=5 | | -1(n*n+3)=2(-4*3) | | 240=128t-16t^2 | | 1/2x-1/5=-10 | | 2(0.36x+11d)= | | -5(x+3)-8=-23 | | p=0.007*4600 | | -x+2x-12=5 | | 16x-1y= | | -1(3*3)=2(-4*3) | | 23x-5+21x+5=23x-5+21x+5s | | 15=-3(n-2)-6 | | y+8=-5(x-3) | | X(2+9x)=0 | | 6m-4=7m+7-m | | -8(9x+9)+6= | | 15-(4v+4)=-4v-11 | | 5x+x+60=90 | | 6+(3+b)= | | 4(4-2x)=24-4x | | 5x+2y+2=80 | | 2*2-18x=0 | | 5+2n-3n=8 | | A=zm+zform | | -8x-62=64-2x |

Equations solver categories